The influence of LiH and TiH2 on hydrogen storage in MgB2 II. XPS study of surface and near-surface phenomena. (1st January 2022) - Snider, J.L.; Mattox, T.M.; Liu, Y.-S.; Wan, L.F.; Wijeratne, P.; Allendorf, M.D.; Stavila, V.; Wood, B.C.; Klebanoff, L.E.
Abstract: Mg(BH4 )2 is a promising solid-state hydrogen storage material, releasing 14.9 wt% hydrogen upon conversion to MgB2 . The rehydrogenation of MgB2 is particularly challenging, requiring prolonged exposure to high pressures of hydrogen at high temperature. Here we report an XPS study probing the influence of LiH and TiH2 on the hydrogen storage properties of MgB2 in the surface and near-surface regions, as a complementary investigation to a preceding study of the bulk properties. Surface and near-surface properties are important considerations for nanoscale and bulk hydrogen storage materials. If there are reactions occurring at the surface that modify the chemical composition in the near-surface region, species diffusion can alter the chemical composition even deep into the bulk of the material. For LiH/MgB2, metastable LiH–B and LiH–Mg species are produced that are more reactive than Bulk MgB2 . With prolonged glovebox storage, the LiH/MgB2 material shows increased reactivity towards O and C and enriched levels of Li and B in the near-surface region. In addition, Li induces the growth of Li2 CO3 in the surface and near surface regions. Exposing LiH/MgB2 to hydrogen at 700 bar and 280 °C for 24 h produces borohydride at a temperature 100 °C below the threshold for bulk MgB2 hydrogenation. In a specifically surface process with macroscopic implications, the hydrogenation conditions also cause Li2 CO3 to react with boron hydroxide in the sample to form a Li-deficient glassy lithium borate melt at the interfaces of the particles, bonding them together. Subsequent heating to 380 °C dehydrogenates the borohydride and eliminates the Li-deficient glassy lithium borate. The LiH/MgB2 material is not reversible because desorption does not lead back to LiH/MgB2, but rather to elemental B and Mg metal in the near-surface region. In contrast to LiH, TiH2 does not react with MgB2, despite the favorable thermodynamics for destabilization via TiB2 formation. Furthermore, high pressure hydrogenation yields only unreacted TiH2 and MgB2 in the surface and near-surface regions. Thus, added TiH2 provides no benefit to MgB2 hydrogenation, in agreement with the findings of the preceding bulk study. Highlights: For LiH/MgB2, metastable LiH–B and LiH–Mg species are produced that are more reactive than Bulk MgB2 . LiH/MgB2 has increased reactivity with O and C and enriched levels of Li and B near the surface with prolonged storage. Added LiH induces the growth of Li2 CO3 that affects the physical characteristics of the bulk material.